Swimming with Swimsuit and Wetsuit at Typical vs. Cold-water Temperatures (26 vs. 18 ℃) - Gay, Ana; Zacca, Rodrigo; Abraldes, J. Arturo; Morales-Ortíz, Esther; López-Contreras, Gracia; Fernandes, Ricardo J.; Arellano, Raúl (International Journal of Sports Medicine, 2021)
This study aimed to compare three swimming conditions in a swimming flume with water at 26 ℃ (using swimsuit) and 18 ℃ (randomly with swimsuit and wetsuit). Seventeen swimmers (32.4±14.7 years old, 175.6±0.06 cm height, and 70.4±9.8 kg body mass) performed three bouts until exhaustion at a 400-m front crawl pace (24 h intervals). ANOVA repeated measures compared the experimental conditions. Swimming at 26 ℃ with swimsuit evidenced a higher metabolic demand (total energy expenditure; (E)), comparing to 18 ℃ swimsuit (p=0.05) and with 18 ℃ wetsuit (p=0.04). The 26 ℃ swimsuit condition presented higher peak oxygen uptake (VO2peak), blood lactate concentrations ([La-]peak), rate of perceived exertion (RPE), maximal heart rate (HRmax), anaerobic lactic energy (AnL), E, energy cost (C), V̇O2 amplitude (Ap), and stroke rate (SR), but lower stroke length (SL) and stroke index (SI) than 18 ℃ wetsuit. The 18 ℃ swimsuit condition (comparing to wetsuit) lead to higher V̇O2peak, [La-]peak, HRmax, E, C, Ap, and SR but lower SL and SI. Swimming at aerobic power intensity with swim and wetsuit at 18 ℃ does not induce physiologic and biomechanical disadvantages compared to 26 ℃. The results suggested that the use of wetsuit might increase performance at 18 ℃ water temperature for competitive master swimmers. Its use is thus recommended in open water swimming competitions when the water temperature is 18–20 ℃.
Keywords: wetsuit; energetics; biomechanics; swimming flume; open water; neoprene